Reliability analysis of breaker arrangements in high voltage stations: A fault tree approach - Liu, Zongyu (My University, 2008)
State Enumeration technique for reliability evaluation is the process of selecting and assessing the impact of all possible contingencies in a given system. It starts with first order failure states to higher orders depending on the resolution requirement. In general higher order failure states do not contribute significantly to the results and are usually neglected from an engineering viewpoint. Fault Tree Analysis (FTA) is a deductive analyzing technique that allows assessing the reliability of complex systems. FTA has been used in the nuclear power, aerospace and railway industries for evaluating the safety and reliability of complex systems. In an FTA analysis, it is postulated that the system has failed in a certain way (top event) and an attempt is made to find out what modes of subsystems behaviours contribute to this failure. In this thesis the reliability of high voltage breaker arrangements is studied using two alternative techniques implemented in two different simulations tools, namely Subrel and Riskspectrum. Dynamic state enumeration and fault tree analysis are used to perform reliability studies of two breaker arrangements. The breaker-and-a-half and double-breaker-double-bus arrangements are assessed and compared. The thesis introduces a modeling technique for analyzing breaker arrangements via fault tree. The modeling technique and corresponding results from the fault tree analysis are validated against those obtained from Subrel. Uncertainty in reliability data is taken into consideration by randomizing failure rate and time to repair in Riskspectrum. The reliability performance of breaker arrangements is compared and discrepancies are explained. It is concluded that the reliability of a breaker and half arrangement is in principle equal to that of a double breaker double bus.
Keywords: Elkraftteknik; Electric power engineering